2022
DOI: 10.1007/s00404-022-06479-3
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of pregnant women with severe COVID-19 requiring extracorporeal membrane oxygenation (ECMO): a case series and literature review

Abstract: Purpose Pregnant women with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have a higher risk of hospitalization, admission to intensive care unit (ICU) and invasive ventilation, and of acute respiratory distress syndrome (ARDS). In case of ARDS and critical severe coronavirus disease 2019 (COVID-19), the use of extracorporeal membrane oxygenation (ECMO) is recommended when other respiratory support strategies (oxygen insufflation, non-invasive ventilation [NIV], invasive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 37 publications
0
32
0
2
Order By: Relevance
“…It is highly likely forthcoming data from the period 2020 to present (including cases associated with the COVID-19 pandemic) will demonstrate a marked increase in use of ECMO in pregnancy, further elucidating maternal outcomes. 15 In addition, several centers are actively linking maternal and neonatal records for data collection, which should allow for improved study of the relationship of maternal ECMO to neonatal outcomes.…”
Section: Research Implicationsmentioning
confidence: 99%
“…It is highly likely forthcoming data from the period 2020 to present (including cases associated with the COVID-19 pandemic) will demonstrate a marked increase in use of ECMO in pregnancy, further elucidating maternal outcomes. 15 In addition, several centers are actively linking maternal and neonatal records for data collection, which should allow for improved study of the relationship of maternal ECMO to neonatal outcomes.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Two case reports have described successful ECMO management, 13 , 14 and a case series of three patients from Italy has demonstrated maternal survival of 67%. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Two case reports have described successful ECMO management, 13,14 and a case series of three patients from Italy has demonstrated maternal survival of 67%. 15 Recently, Barrantes et al 16 presented a case series of nine pregnant or peripartum women with COVID-19 ARDS managed with V-V ECMO. The results of this study are interesting because they are, on the one hand very comparable to our study, but also demonstrate significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, there have been multiple reports of pregnant women infected with severe COVID-19. While it has been reported that extracorporeal membrane oxygenation (ECMO) therapy is useful for severe COVID-19 pneumonia, the optimal timing for the initiation of ECMO and whether or not to continue the pregnancy in women with severe COVID-19 pneumonia remains unclear, as the risk and benefit to both mother and fetus need to be considered [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%